2005
DOI: 10.1016/j.otohns.2005.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Single‐Blind Trial Comparing Ultrasonic Scalpel Tonsillectomy with Tonsillectomy by Blunt Dissection in a Pediatric Age Group

Abstract: US tonsillectomy appears to cause more postoperative pain than BD tonsillectomy in children aged 5 to 13 years undergoing tonsillectomy for recurrent acute tonsillitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 15 publications
1
29
1
Order By: Relevance
“…In a prospective randomized study conducted on adult patients by Parsons et al (2006), radiofrequency tonsillectomy has been reported to decrease postoperative pain compared to electro cautery. In a single-blind randomized study by Oko et al (2005) on pediatric patients, pain after tonsillectomy with blunt dissection was found to be significantly less than tonsillectomy with ultrasonic blades. In the study by Yilmaz et al (2012) on 91 pediatric patients, postoperative pain with thermal welding has been found to be less.…”
Section: Discussionmentioning
confidence: 96%
“…In a prospective randomized study conducted on adult patients by Parsons et al (2006), radiofrequency tonsillectomy has been reported to decrease postoperative pain compared to electro cautery. In a single-blind randomized study by Oko et al (2005) on pediatric patients, pain after tonsillectomy with blunt dissection was found to be significantly less than tonsillectomy with ultrasonic blades. In the study by Yilmaz et al (2012) on 91 pediatric patients, postoperative pain with thermal welding has been found to be less.…”
Section: Discussionmentioning
confidence: 96%
“…Although operating time and blood loss were reduced considerably by the use of electrocautery, postoperative pain remained a significant morbidity [4]. In recent years, several new techniques for tonsillectomy have been proposed such as, harmonic ultrasonic scalpel, coblator, laser or radiofrequency excision, and tonsilloplasty, aiming to less bleeding, decreased operating time and minimum postoperative pain [2,5,6]. Despite the evolving technology and the variety of the devices that have been designed, research continues in order to accomplish these goals.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty percent of all 89 studies reported results with fewer than 90 subjects. Eight of the 89 studies (9%) reported study size with power analyses [7,21,32,46,54,55,62,63].…”
Section: Study Sizementioning
confidence: 99%